POTENCY OMEGA-9 OLEIC ACID IN THE AVOCADO FRUIT MESOCARP CHOLESTEROL LOWERING BLOOD SERUM - Eny Hartadiyati Wasikin Haryanti (Universitas PGRI Semarang, 2011)
Avocado is high in fat, contained in the development of forms of mono-unsaturated fats (monounsaturated fatty acids), namely omega-9: 72.2% oleic acid. This fatty acid configuration can inhibit the absorption of cholesterol in intestines and not easily oxidized than linoleum and lino-lenic acid. Therefore, it improves blood serum cholesterol levels. This study aims to analyze the changes in HDL and LDL cholesterol in the serum of mice?é?á hypercholesterolemic effect of omega-9 oleic acid on the avocado fruit mesocarp. The design of this study is the pre and post with control group (ran-domized control pre post test design). Animal experiment (Rattus norve-gicus strain Sprague Dawley) was given treatment: P0 group was given standard food + 0 mg avocado fruit mesocarp; P1 groups was given stan-dard food + avocado fruit mesocarp dose 1.35 g / day; the group P2 was given standard food + avocado fruit mesocarp 2.7 g / day; groups P3 of rats was given standard food + avocado fruit mesocarp dose 4.05 g / day. The result showed a decrease of ?é?áblood serum levels of LDL cholesterol, and elevated levels of blood serum HDL cholesterol, which is significant at 5% probability level. The conclusion is oleic acid omega-9 in the avocado fruit mesocarp?é?á has the potential to lower LDL cholesterol blood serum of rats. Key words: omega-9 oleic acid, cholesterol, avocado, blood serum, LDL, HDL.